PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGUKURAN SUSTAINABILITY REPORT (StudiEmpirisPada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Aniyatur Rokhmah, 13.05.51.0138 (Students Journal of Economic and Management, 2017)
This study examines the effect of financial performance, firm size and corporate governance on sustainability report. This research was conducted at Burs Efek Indonesia by using unit of analysis of manufacturing company which have gone public. Sampling method using purposive sampling with research period year 2013 until 2015. Relationship and or influence between variables is explained by using method of multiple regression analysis. The results showed that financial performance and firm size have a significant positive effect on sustainability report. While corporate governance has no significant effect on sustainability report. Keywords: Financial Performance, Company Size, Corporate Governance and Sustainability Report